Case report and literature review: Primary leiomyosarcoma of the bone in the trochanteric region of the femur - Wu, Zhonghan; Cheng, Li; Cao, Qiliang; Ye, Shuming; Yu, Shuisheng; Sun, Min; Jing, Juehua (Frontiers in Surgery, 2023)
Background: Primary leiomyosarcoma of the bone (LMSB) is an extremely rare, invasive, and highly destructive primary osteosarcoma with limited treatment options and poor prognoses. Only a few case reports of LMSB have been described because of its rarity. Therefore, clinicians have a limited understanding of its diagnosis, treatment, and prognosis, and the final diagnosis depends on histopathological findings. In this report, we describe a rare case of primary LMSB in the trochanteric region of the femur. Reporting this case may increase the dissemination and understanding of information regarding LMSB and provide a reference for the diagnosis and treatment of similar cases. Case presentation: A 63-year-old woman presented with pain and limited movement of the left hip, which had lasted for 3 months, with no history of trauma or illness. Plain radiography and computed tomography revealed a solitary osteolytic lesion in the left femur’s trochanteric area with focal cortical destruction. Magnetic resonance imaging findings suggested the lesion’s invasion into the bone cortex, forming a soft tissue mass, although no distant positive findings were observed on a whole-body bone scan. A bone tumor puncture biopsy was performed to obtain a final diagnosis, and histopathological evaluation revealed left femoral intertrochanteric leiomyosarcoma, classified as G1T2M0 and staged as IB (extracompartmental low-grade malignant) according to the Enneking staging system. Thus, we performed extensive debridement and left hip arthroplasty. Postoperative chemotherapy was administered, and the patient was followed up for 4 years. Four years later, the patient’s left hip pain had resolved, joint activity was good, and no signs of recurrence or distant metastasis of the bone tumor were noted. Conclusions: For proximal femoral Enneking stage IB LMSB, extensive tumor resection combined with tumor prosthesis replacement may be an effective treatment method to prolong the patient’s lifespan and to restore joint function.